2020
DOI: 10.5194/tc-14-3629-2020
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the grounding zone of Larsen C Ice Shelf, Antarctica, from ICESat-2 laser altimetry

Abstract: Abstract. We present a new, fully automated method of mapping the Antarctic Ice Sheet's grounding zone using a repeat-track analysis and crossover analysis of newly acquired ICESat-2 laser altimeter data. We map the position of the landward limit of tidal flexure and the inshore limit of hydrostatic equilibrium, as demonstrated over the mountainous and hitherto difficult to survey grounding zone of Larsen C Ice Shelf. Since the start of data acquisition in 2018, our method has already achieved a near 9-fold in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 34 publications
(77 reference statements)
0
29
0
Order By: Relevance
“…6), obvious topographical patterns and flat terrain can be found in the mountain environments and ice sheet interior, respectively. On the Antarctic Peninsula, good agreement can be found between the grounding line locations determined from ICESat-2 in Li et al (2020) and the ice shelf limit is visually identified from the shaded relief map (Fig. 6b).…”
Section: General Attributes Of Icesat-2 Demmentioning
confidence: 57%
“…6), obvious topographical patterns and flat terrain can be found in the mountain environments and ice sheet interior, respectively. On the Antarctic Peninsula, good agreement can be found between the grounding line locations determined from ICESat-2 in Li et al (2020) and the ice shelf limit is visually identified from the shaded relief map (Fig. 6b).…”
Section: General Attributes Of Icesat-2 Demmentioning
confidence: 57%
“…We processed the ATL06 elevation data using the same methods described in Li et al (2020). We did not apply the ocean tide correction to ICESat-2 ATL06 elevation and 're-tided' the ocean loading tide.…”
Section: Icesat-2 Data and Processingmentioning
confidence: 99%
“…Following the steps of repeat track generation described in Li et al (2020), the surface elevation, elevation measurement geolocations, and the reference segment geolocations of six ground tracks along each of the 1387 Reference Ground Tracks (RGTs) were categorized into nine distinct repeat-track data groups, including six single-beam repeat-track data groups and three beampair repeat-track data groups (Figs. 4a and 4b in Li et al (2020)). For each repeat-track data group, a 'nominal reference track' was calculated by averaging the locations of reference segments from all repeat tracks inside this data group.…”
Section: Repeat Track Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, its successor, ICESat-2, was launched equipped with an improved laser altimetry system, which is expected to produce height measurements with enhanced accuracy and coverage (e.g., [11]). The first data analyses have shown its potential for cryosphere applications, such as mapping of grounding lines in Antarctica [12] or elevation and mass change assessments for the Greenland and Antarctic ice sheets [11]. However, for smaller glaciated regions like Svalbard, an evaluation of the potential of combining data from both missions through a crossover approach has not been published yet.…”
Section: Introductionmentioning
confidence: 99%